Penguatan Layanan Pendampingan Penulisan Ilmiah untuk Meningkatkan Publikasi Mahasiswa - Rafhi Febryan Putera; Neti Ramayani; Miftahus Silmi Zohro; Ainun Mahfuzah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was motivated by the low level of students’ scientific writing skills, which affected the limited number of publications and participation in thesis examinations. This program aimed to improve students’ scientific writing skills and increase the number of students completing their studies through structured writing assistance. The methods included socialization, training, and intensive mentoring conducted in a participatory approach involving PGSD FKIP Universitas Bengkulu students from January to April 2026. The results showed a significant increase in student participation in thesis examinations from 45% to 75%, along with improvements in both the quantity and quality of scientific articles produced. Qualitatively, students demonstrated better understanding, writing skills, and academic motivation. This program indicates that structured mentoring is effective in enhancing publication productivity and accelerating students’ study completion.